HUMAN PAPILLOMAVIRUS AND ITS NATURE OF INFECTION: AN OVERVIEW - Das, Ranit; Mishra, Vijay; Sharma, Neha; Khurana, Navneet (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Human papillomavirus (HPV) belonging to Papillomaviridae (family of Papillomavirus). HPV infection causes various types of disorders and diseases including cervical, vaginal, anal, penile, oropharyngeal, and lung cancer also cancer in head and neck along with some malignant and benign warts. HPV also found to be responsible for respiratory papillomatosis. Epidermodysplasia verruciformis, an orphan disease termed as tree man disease, is also occurred by the HPV infection. Vaccines show benefit nowadays. Some surgery and adjuvant therapy is also showing response in the treatment of HPV caused cancers. In this abstract, we summarized the types, structures, genomic organization, mode of transmission of the virus along with type of infections, and protection and modern treatment approaches.